Tinjauan Pustaka Sistematis_Proteksionisme dan Dinamika Perdagangan Internasional - Irvansyah, Mohamad; Irwan Ramdhan, Mohamad; Panjaitan, David; Nisa, Khairun (Program Studi Manajemen FEBM UMRAH, 2025)
In the past decade, the resurgence of protectionist policies has emerged as a major challenge to the stability of international trade. The trade conflict between the United States and China, the COVID-19 pandemic, and the increasing imposition of tariff and non-tariff barriers have marked a shift from the era of globalization towards a trend of deglobalization. This study aims to systematically examine the impact of protectionism on the dynamics of international trade with a particular focus on three key countries: the United States, China, and Indonesia. This research employs a Systematic Literature Review (SLR) approach and adheres to the PRISMA 2020 guidelines to ensure that the review process is systematic, transparent, and replicable. Literature was collected from three major academic databases—Scopus, ScienceDirect, and Google Scholar—using inclusion criteria such as articles published between 2020 and 2025, written in English or Indonesian, and peer reviewed. A content analysis was conducted on 30 selected journal articles to identify patterns, key findings, and policy implications. The analysis reveals that protectionism has significantly affected global supply chains, energy consumption, and macroeconomic stability in various countries. The US–China trade war in particular has created distortions in bilateral trade and triggered policy uncertainty. Meanwhile, Indonesia faces challenges from both external shocks and internal protective measures that influence its export competitiveness. The study recommends the importance of export market diversification, enhancement of value-added exports, and strengthening of multilateral cooperation to mitigate the negative impacts of protectionism and foster a more equitable and sustainable global trading system.